2019
DOI: 10.3390/ma12040554
|View full text |Cite
|
Sign up to set email alerts
|

A New, Carbon-Negative Precipitated Calcium Carbonate Admixture (PCC-A) for Low Carbon Portland Cements

Abstract: The production of Portland cement accounts for approximately 7% of global anthropogenic CO2 emissions. Carbon CAPture and CONversion (CAPCON) technology under development by the authors allows for new methods to be developed to offset these emissions. Carbon-negative Precipitated Calcium Carbonate (PCC), produced from CO2 emissions, can be used as a means of offsetting the carbon footprint of cement production while potentially providing benefits to cement hydration, workability, durability and strength. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In fact, Climate change of 1 kg of Portland cement is 0.96 kg CO 2 eq while for the nano-added cement it is 0.3 kg CO 2 eq , meaning a reduction of 69 % in the CC category. McDonald et al, (2019) [38] stated that the exploitation in the cement industry of the carbon dioxide contained in the flue gas to produce calcium carbonate can reduce the carbon footprint of blended Portland cements by more than 25 %. In spite of their promising results, they recommend a full LCA of calcium carbonate cements in order to ger more accurate results.…”
Section: Lca Of Cementmentioning
confidence: 99%
“…In fact, Climate change of 1 kg of Portland cement is 0.96 kg CO 2 eq while for the nano-added cement it is 0.3 kg CO 2 eq , meaning a reduction of 69 % in the CC category. McDonald et al, (2019) [38] stated that the exploitation in the cement industry of the carbon dioxide contained in the flue gas to produce calcium carbonate can reduce the carbon footprint of blended Portland cements by more than 25 %. In spite of their promising results, they recommend a full LCA of calcium carbonate cements in order to ger more accurate results.…”
Section: Lca Of Cementmentioning
confidence: 99%
“…Further, previous studies have shown that nano CaCO 3 can provide comparable benefits to other higher-cost nanomaterials [ 23 , 24 ]. Additionally, nano CaCO 3 can be produced within the cement plant utilizing the waste CO 2 using an integrated approach for green and economical cement production [ 25 , 26 ], thus is an environment-friendly technology. This approach will help mitigate the adverse impacts of cement plants on the environment while also providing extra revenue for the cement plant owners.…”
Section: Introductionmentioning
confidence: 99%
“…10 Industrially, Na 2 CO 3 is mainly produced through the Solvay process which requires large amount of thermal energy and CaCO 3 calcination. 33 The produced Na 2 CO 3 can have several uses in the industry: (1) for flue gas CO 2 sequestration through the production of NaHCO 3 , 34,35 (2) as an alkali activator for cements, either directly or in the production of activators such as sodium silicates, 36,37 (3) in the production of precipitated calcium carbonate from brine for use as a cement admixture, 38 (4) to regenerate the necessary NaOH, 21,[39][40][41] and/or (5) sold for the manufacture of other commodities (e.g. glass).…”
Section: Additional Discussionmentioning
confidence: 99%